Status of the commissioning of the X-band injector prototype for AWAKE Run 2c - Mușat, V; Burrows, P; Calderon, M; Gschwendtner, E; Granados, E; Doebert, S; Latina, A (JACoW Publishing, 2024)
The status of commissioning of the electron injector intended for the next phase of the proton driven wakefield experiment, Advanced Wakefield Experiment (AWAKE), is presented, showing first results from operating the brazingfree electron gun. To provide a high-quality electron beam, the UV laser was centered on the copper cathode, and a novel beam-based alignment of the focusing solenoid was performed. Measurements of the beam parameters and working points are addressed. The electron gun is shown to provide a high quality, stable and reproducible beam.